P62/SQSTM1—Dr. Jekyll and Mr. Hyde that prevents oxidative stress but promotes liver cancer. Issue 15 (6th August 2016) - Taniguchi, Koji; Yamachika, Shinichiro; He, Feng; Karin, Michael
Abstract : p62/SQSTM1 is a multifunctional signaling hub and autophagy adaptor with many binding partners, which allow it to activate mTORC1‐dependent nutrient sensing, NF‐κB‐mediated inflammatory responses, and the NRF2‐activated antioxidant defense. p62 recognizes polyubiquitin chains via its C‐terminal domain and binds to LC3 via its LIR motif, thereby promoting the autophagic degradation of ubiquitinated cargos. p62 accumulates in many human liver diseases, including nonalcoholic steatohepatitis (NASH) and hepatocellular carcinoma (HCC), where it is a component of Mallory–Denk bodies and intracellular hyaline bodies. Chronic p62 elevation contributes to HCC development by preventing oncogene‐induced senescence and death of cancer‐initiating cells and enhancing their proliferation. In this review, we discuss p62‐mediated signaling pathways and their roles in liver pathophysiology, especially NASH and HCC. Abstract :